Mapping of antibiotic resistance in Multi-Drug Resistance Tuberculosis at RSUD Arifin Achmad, Riau Province - Andralia Mayangsasati; Sri Sundari (Universitas Muhammadiyah Surabaya, 2022)
Tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis. Resistance is a condition where an antibiotic is not able to kill Mycobacterium tuberculosis. The type of research used is descriptive with a mixed-method approach. It was found that most MDR-TB patients were male (67.2%), aged 41-50 years (26.9%), and lived in Pekanbaru City (65.7%). There were 30 patients (44.8%) who underwent microscopic examination, 12 patients (44.4%) who had a previous medical history of TB disease who had been informed finished taking medication by their doctors. Nine patients (33.3%) with a history of inadequate TB treatment. Three patients (11.1%) were confirmed as a treatment failure. Three patients (11.1%) were primary TB and confirmed the result of laboratory tests for resistance to anti-TB drugs. MDR TB patients who smoke were nine patients (33.3%), and DM patients were two people (7.4%). So, information about the characteristics of Multi-Drug Resistance Tuberculosis is needed, and it is hoped that appropriate treatment can be given